Analyzing the impact of transitioning to a green economy on major polluting industries - Jungwirth, Jan; Formánek, Tomáš; Sokol, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The focus of this thesis is the impact of energy mix composition on the economic performance of selected sectors across European Union. The analysis focuses on four NACE sectors, mining and quarrying (B), manufacturing (C), construction (F), and accommodation and food services. The period covered is from 2008 to 2022 with 25 EU countries as the examined sample. Gross Value Added (GVA) serves as the dependent variable, while independent variables include structural business statistics, macro economical indicators and the consumption of energy sources like renewable, nuclear and fossil energy source, with energy consumption by source serving as a proxy for relevant policies affecting the sectors. To properly estimate the impacts, both traditional panel models and spatial panel models have been used. Mainly the fixed effects specification was employed with both spatial lag and spatial error specification applied. The results of analysis support the idea that different energy source do have impact on all four sectors. Sector B and F are affected negatively by positive changes in renewable energy and sector C affected positively by those changes, while sector I is affected by fossil fuels in a positive way. The findings overall highlight the necessity to account for policy impacts on different industries and to act accordingly.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses